ผลการจัดการเรียนรู้ตามแนวคิด STEAM Education โดยใช้ปัญหาเป็นฐานเพื่อพัฒนาทักษะและกระบวนการทางคณิตศาสตร์ สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 1 - ศรีบุญ, สุนารี; โพธิ์เงิน, วิสูตร (Journal of Education Studies, Chulalongkorn University, 2019)
The research purposes were: 1) to compare student’s mathematical skills before and after learning through STEAM education approach integrated with problem–based learning (PBL); 2) to study mathematical skills and processes of students after learning through STEAM education approach integrated with problem-based learning (PBL); and 3) to study the satisfaction of the students after learning through STEAM education approach integrated with problem-based learning (PBL). The sample group in this research is comprised of 30 Mathayom 1/1 students in the Danthaptakoratuppatham School who were studying in the 2nd semester of B.E. 2560. The research tools include: 1) learning management plans; 2) achievement tests; 3) a behavior observation form; and 4) a questionnaire for investigating students’ opinions toward the STEAM education approach integrated with problem-based learning (PBL). The mean, standard deviation (SD) and test (t-test) were applied for data analysis. The research results can be concluded that: 1) the student’s mathematical skills after the learning through STEAM education approach integrated with problem-based learning (PBL) were significantly higher than those before studying at the .05 level; 2) the student’s behaviors on mathematical skills and processes were positive at a high level; 3) the student’s opinions toward the learning through STEAM education approach integrated with problem-based learning (PBL) were positive at a high level.